Alloy design of V-based hydrogen permeable membrane under given temperature and pressure condition. (31st August 2017) - Suzuki, A.; Yukawa, H.; Nambu, T.; Matsumoto, Y.; Murata, Y.
Abstract: For alloy design of hydrogen permeable membrane, it is important to control pressure–composition–isotherm (PCT curve) in an appropriate manner in order to obtain high hydrogen permeability with strong resistance to hydrogen embrittlement. Based on this concept, V-based alloy membranes are designed under some given pressure conditions at a temperature in view of the partial molar enthalpy change, Δ H ¯ 0.2, and entropy change, Δ S ¯ 0.2, of hydrogen for hydrogen dissolution. It is demonstrated that the PCT curve can be controlled very precisely in view of Δ H ¯ 0.2 and Δ S ¯ 0.2 . Also, the required membrane area to obtain 300 Nm 3 h −1 of hydrogen flow is estimated. It is found that, in view of the membrane area, it is favorable to apply at least 400 kPa of hydrogen pressure at feed side. Highlights: A concept for alloy design of H2 permeable membrane has been applied for V–Fe system. In this concept, hydriding property must be controlled appropriately. In view of the thermodynamic parameters, hydriding property can be controlled. Correlation between membrane area and applicable hydrogen pressure is discussed. A concept for scale up of the membrane area is obtained.